Randomized clinical trial on effectiveness of modified Akinosi technique in mandibular molars with symptomatic irreversible pulpitis during endodontic therapy - Aarti Bohora; Rohan Bhambar; Dheeraj Kalra; Vinay Sharma; Padmaja Sirsat; Anuj Bhardwaj; Alexander Maniangat Luke; Krishna Prasad Shetty; Ajinkya M. Pawar; Mohmed Isaqali Karobari (Scientific Reports)
Abstract The aim of the study is to investigate the effectiveness of the modified Akinosi technique [MAT] in endodontic management of mandibular molars with symptomatic irreversible pulpitis, and to compare it with the standard inferior alveolar nerve block for effective pulpal anesthesia. A total of 80 clinically healthy patients of both genders, between 16 and 65 years, diagnosed with symptomatic irreversible pulpitis in mandibular first and second molars were included in the study. The subjects were divided into two groups. Group A received nerve block and pulpal anesthesia through Inferior Alveolar Nerve Block technique, while Group B received nerve block through MAT with 2% lignocaine containing 1:200,000 adrenaline. All endodontic treatments were performed in a single visit. We evaluated the presence of pain during various phases of endodontic treatment with Visual Analog Scale. The pain level was registered at the end of the following phases of the endodontic treatment: 1. During access cavity preparation; 2. While determining working length for all the root canals; 3. During cleaning and shaping of root canals. In Group B, 80% of patients reported no pain, as compared to 51% in Group A. MAT is an effective method for achieving pulpal anesthesia in endodontic treatment of symptomatic irreversible pulpitis.